Breve panorama de la psicología educacional en el Perú - Meza, Aníbal (1990)
This paper reviews the origin and development of educational psychology in Peru. The following topics and fields of study are presented: special education, early stimulation, psychoeducacional research (basic and applied). Theoretical parers and literature reviews are included, as well as technological production (textbooks and psychological testing). At the end an overall assessement of the field is discussed.